Added value of antiphosphatidylserine/prothrombin antibodies in the workup of thrombotic antiphospholipid syndrome: Communication from the ISTH SSC Subcommittee on Lupus Anticoagulant/Antiphospholipid Antibodies. (14th July 2022) - Vandevelde, Arne; Chayoua, Walid; de Laat, Bas; Moore, Gary W.; Musiał, Jacek; Zuily, Stéphane; Wahl, Denis; Devreese, Katrien M. J.
Abstract: Background: Diagnosis of antiphospholipid syndrome (APS) requires persistent presence of lupus anticoagulant (LAC), anticardiolipin (aCL) IgG/IgM, or anti‐β2 glycoprotein I (aβ2GPI) IgG/IgM antibodies. Other antiphospholipid antibodies (aPL) such as antiphosphatidylserine/prothrombin antibodies (aPS/PT) are promising in assessment of thrombotic APS (TAPS). Aim: To evaluate the added value of aPS/PT IgG and IgM in TAPS. Material and Methods: aPS/PT IgG/IgM, aCL IgG/IgM, aβ2GPI IgG/IgM, and LAC were determined in 757 patients (TAPS and controls). aPS/PT cut‐off values were calculated, and aPS/PT titers and positivity were compared between TAPS and controls, type of thrombosis, and antibody profiles. Likelihood ratios (LR), odds ratios (OR), and aPL score were determined. Results: aPS/PT IgG and IgM were associated with TAPS and triple positivity. In‐house calculated cut‐offs were higher for IgM (43 units), compared to manufacturer's cut‐off (30 units). Thresholds of 90 (IgG) and 200 (IgM) units were determined as high‐titer cut‐off. Higher aPS/PT titers were observed in triple positive patients and showed higher LR and OR for TAPS. aPS/PT was independently associated with TAPS when adjusted for aCL/aβ2GPI, but not when adjusted for LAC. In isolated LAC positive patients, aPS/PT was positive in 27.1% TAPS patients and in 77.3% patients with autoimmune disease. Diagnostic value of aPL score did not differ with and without including aPS/PT. Conclusion: aPS/PT positivity, especially with high antibody titer, is associated with TAPS diagnosis. Analysis on top of current laboratory criteria is not essential in TAPS diagnosis, but aPS/PT could be useful in patients with thrombosis and a double positive aPL profile (aCL+/aβ2GPI+).